Investigating the Association Between Serum Vitamin D Deficiency and Idiopathic Benign Paroxysmal Positional Vertigo - Jignesh Dhirubhai Dhameliya; Umesh Kumar Chandra; Sumit Kumar Vishwakarma; Dattaprasad Ganganpalli; Archana Verma (International Clinical Neuroscience Journal, 2020)
Background: It is suggested that there is a positive association between vitamin D deficiency and benign paroxysmal positional vertigo (BPPV). We suggest, as a hypothesis, there is a positive association between vitamin D deficiency and BPPV. The current study aimed to investigate the association between vitamin D levels and BPPV. Methods: The present observational case-control study was planned and conducted on 100 participants (50 cases and 50 controls) in the Department of Neurology, Choithram Hospital & Research Center (CHRC), Indore, MP, India, from January 2018 to December 2018. All consecutive patients with diagnosis of idiopathic BPPV who were above the age of 18 years with a negative neurological status were included. Analyses were performed using SPSS software version 10. Results: BPPV was more common among those aged 50 to 70 years (64%). Out of 100 participants, 72 (72%) had vitamin D deficiency, in which 40 (80%) were cases and 32 (64%) were controls. 32 (64%) patients had posterior canal involved, out of them 20 (40%) were females and 12 (24%) were males, and in both groups posterior canal was more involved. Canal involvement according to gender was not statistically significant (P value=0.45). Mean vitamin D level for cases and controls was 34.9 and 46.5 nmol/L, respectively, and this difference was statically very significant with a p-value of 0.01 (P value < 0.05). Conclusion: According to the findings, there is a statistically significant association between vitamin D3 deficiency and Idiopathic BPPV. It can be noted that vitamin D3 deficiency may be a risk factor for the BPPV.